Retracing Ethnic Cleansing Throughout the Trail of Tears - Meriem, SLIMANI; NaouelS, SEBAA (جامعة الوادي - University of Eloued, 2023)
In an attempt to unravel the deliberately-shaded history in the American civilization that was built on the ruins of the one of the indigenous people in the new world. This study aims at retracing the effects of ethnic cleansing on Native Americans throughout retracing “the Trail of Tears” by revealing the repercussions and latent role of forced displacement in obliterating their identity and entity. Through employing both descriptive research method and Historical Source Analysis technique , evidence of the former’s theoretical reviewing of literature have been affirmed through the latter’s six skills by analysing the Indian Removal Act 1830. Those results unfold one of the darkest sides of the American history within this legislation that abolished much of the cultural identity of Native Americans and concealed their own ways on their usurped homeland in years to come. في محاولة لسبر أغوار الحضارة الأمريكية التي قامت على أنقاض حضارة السكان الأصليين بالعالم الجديد، سعت الدراسة الحالية لإعادة تقفي آثار التطهير العرقي للهنود الحمر عبر حدث درب الدموع في التاريخ الأمريكي و ذالك من خلال إبراز انعكاسات الترحيل القسري و دوره الكامن في طمس هوية وكيان السكان الأصليي ن اللذان عني بهما المبحث النظري لهذه الورقة البحثية . تم اعتما د أسلو ب البح ث الوصفي النوعي في تحليل نمط حيا ة السكان الأصليين، إضاف ة إلى تحليل الوثيقة التاريخية لقانون الإبعا د الهندي لعا م 1830 كأداة بحث عملية بجانبها التطبيقي والتي أفضت نتائجها أن النقطة المظلمة في تاريخ الولايا ت المتحدة تكمن وراء هذا القانون الذي حقر بشدة من الهوية الثقافية للهنود الحمر وأعا د تشكيل مجتمعهم القبلي ماضيا و حاضرا .
Keywords: Ethnic Cleansing , Historical Source Analysis , Indian Removal Act , Native Americans , Trail of Tears; الهنو د الحمر , قانون الإبعا د الهند ي , در ب الدموع , التطهي ر العرقي , تحليل وثيقة تاريخي ة .